Leakages from Public Distribution System (PDS) and the Way Forward - Ashok Gulati and Shweta Saini (INDIAN COUNCIL FOR RESEARCH ON INTERNATIONAL ECONOMIC RELATIONS, 2015)
The public distribution system (PDS) has been one of the main policy instruments of the Government of India (GoI) to provide food security to the people of this country, especially the vulnerable ones. The recently enacted National Food Security Act (NFSA), 2013, also relies heavily on it to deliver even more grain at highly subsidized prices to 67 percent of population. But the existing PDS system has been highly "leaky", with large amounts of grains (40 to 50 percent) being pilfered and diverted to open market. Also, the existing PDS delivers better in better-off states rather than in those where there is concentration of poor, raising issues of equity. Further, the food subsidy bill is ballooning, with Rs 1.15 lakh crores budgeted for FY 2015 plus (unbudgeted) arrears of more than Rs 50,000 crores. The big challenge, therefore, is how to ensure that large sums of money being spent by GoI on PDS deliver food security more efficiently, with much lesser leakages and in a more cost effective manner. In an effort to highlight the inefficiency and iniquitous nature of the existing PDS, the present paper estimates the proportion of grain that was diverted/leaked from the PDS grain-chain in 2011-12. This is done by mapping the difference between the grains off-taken by states from the Central pool and the grain consumed by the PDS beneficiaries. It also studies how tuned is the PDS welfare delivery system to the country’s poor. The paper finds that at an all-India level, 46.7 per cent or 25.9 MMTs of the off-taken grain did not reach the intended PDS beneficiaries in 2011-12. The percent share of total leakage increased with states where greater percent of India’s poor resided (five states: UP, Bihar, MP, Maharashtra and West Bengal, which are home to close to 60% of India’s poor accounted for close to 50% of the total grain leakage in the country in the year 2011-12). While some experts (Himanshu and Sen, 2011) pitch for near universal PDS to plug leakages, and NFSA argues for end to end computerization and setting up of vigilance committees and courts, this paper makes a case for shifting the support to poor from highly subsidized price policy to income policy of cash transfers through Jan-Dhan yojana dovetailing UID of Aadhaar scheme. We also argue that this is the best global practice, can plug leakages, reach the vulnerable segments of population, not interfere with markets of food, and save more than Rs. 30,000 crores annually to the government of India under the most likely scenario, while still giving a better deal to consumers. The saved resources can be ploughed back as investments in water (irrigation), rural roads and agri-R&D that could deliver food security, directly or indirectly (through increased incomes), to people of this country in a more sustainable manner.